Os efeitos de ações formativas nas interações mediadas pela comunicação alternativa por alunos com Tea - Reis, Henrique de Candia (Universidade Federal de São Carlos, 2021)
Augmentative and Alternative Communication (AAC) aims to expand the communicative possibilities of people with complex communication needs, in which their abilities to dialogue and to make themselves understood are impaired. Requiring visual and/or gestural graphic resources that complement or replace compromised or absent oral language. Alternative communication has, above all, the need for competent and proactive interlocutors with attitudinal accessibility (regarding the perception of the other and free from prejudices, stigmas, stereotypes and discrimination) so that there is a real interest in the communicative development of the person who does not have functional speech, going much further, therefore, of the only recursive approach in relation to its users. Autism Spectrum Disorder (ASD), according to the DSM-V, is a neurodevelopmental condition that is characterized by socio-communicative impairments and the presence of repetitive and stereotyped behaviors. The new definition emphasizes the correlation between deficits in social skills and communication deficits. The present study identify how the interactions between a non-verbal student with ASD and his teachers occurred in the school and verify if the offer of his AAC resource, with direct instructions to both, regent and support teachers, could contribute to the advancement of participation in the school context.The type AB study took place in an elementary school in the city of Ribeirão Preto - SP. Participants in the Baseline and Intervention were: a 10-year-old student with ASD and user of the Alternative Communication Program PECS-Adapted, at the beginning of phase 4 in this program. And his four teachers from regular school. The frequencies of student/teacher communicative interactions were collected during 21 minutes of daily observations during regular classes of the participating teachers with the participating student present. The communicative interactions that occurred without the Alternative Communication resource were observed and, from the fifth observation session, the student's Alternative Communication resource was inserted. The resource used in the intervention followed Incidental Teaching strategies to take advantage of natural communicative situations during the observed contexts and that provided direct engagement of the student and the participating teachers with the CAA. It was desired with this, to provide a strategy of Continuing Education to teachers on the benefits of AAC. The results showed a decrease in conduct disorders associated with the student and positive behavioral changes by teachers as interlocutors after the intervention with Alternative Communication. Thus, the study can contribute as an account of strategies that can strengthen the performance of teachers involved in the schooling of students with ASD and enrich the inclusive experience in this context.
The effects of formative actions in mediated interactions by alternative communication by students with Asd
Keywords: Educação especial; Transtorno do espectro do autismo; Inclusão escolar; Comunicação alternativa e ampliada; PECS-adaptado; Special education; Educational inclusion; Autism spectrum disorder; Augmentative and alternative communication; Adapted PECS; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO